REAL WORLD DATA : ANTIVIRUS SELECTION IN COVID-19 PATIENTS AT PKU MUHAMMADIYAH GAMPING HOSPITAL - Damayanti, Hazena Misgi; Perwitasari, Dyah Aryani; Risdiana, Irma; Kuluq, Muhammad Husnul (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2024)
COVID-19 is a disease that requires antivirals, such as favipiravir and remdesivir, which have been recommended in Indonesia. Choosing the right antiviral agent can affect the length and total cost of hospitalization. The impact of COVID-19 can cause a decline in health and the economy, if not treated effectively. This study aimed to determine the average length of hospitalization and total cost of hospitalization for COVID-19 patients based on the selection of favipiravir and remdesivir antivirals at the PKU Muhammadiyah Gamping Hospital from August 2022-August to 2023 based on real world data. The research method was Observational research with a descriptive research design and retrospective data collection was used. During this period, 306 patients were diagnosed with COVID-19. A total of 171 patients met the inclusion criteria, including 130 patients using favipiravir antivirus and 41 patients using remdesivir antivirus. The results of this study are the average length of hospitalization of the patient group with antiviral favipiravir was 4.1 days and the patient group with antiviral remdesivir was 5 days and the average total cost of hospitalization of the patient group with antiviral favipiravir was IDR 12,377,415 and the average total cost of the patient group with antiviral remdesivir was IDR 14,428,132. The conclusion of this study is that the use of favipiravir antiviral therapy is more effective when viewed from the perspective of length of hospitalization and total cost of hospitalization; therefore, these results can be applied under the same conditions in the treatment of COVID-19.